Pengaruh Inovasi Pelayanan SOS MAS (Service on Saturday di Kecamatan Kebomas) terhadap Kepuasan Masyarakat - Natasya Salsabila Pramudita; Eva Hany Fanida; Meirinawati; Trenda Aktiva Oktariyanda (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
The majority of Kebomas District's residents are connected to working hours during government office hours (Monday through Friday), which creates access obstacles in administering public services due to the high population density and busy community life. In response to these time constraints, the SOS MAS (Service On Saturday in Kebomas District) invention was introduced, which offers services on Saturdays. However, the implementation of this innovation still faces challenges in the form of a low social integration rate and a restricted range of public services that have the potential to sway public opinion. The goal of this research is to assess how the SOS MAS innovation affects community happiness in Kebomas District. A quantitative technique with an associative approach is used in this research. Through an unintentional sampling method, questionnaires were given to 86 individuals in order to gather primary data. With the aid of SPSS, the determinant coefficient and a simple linear regression test were used to analyze the data. The study's findings reveal that the SOS MAS invention has a favorable and substantial influence on community happiness. The regression coefficient of 0.969 and a significance level of 0.000 <0.05 support this. The innovation variable accounted for 59.7% of public happiness, while the remaining 40.3% was impacted by variables not included in the study model, according to the coefficient of determination (R2) test. This result supports the notion that the efficacy of service innovation outside of working hours is a major element in boosting happiness for individuals with limited time. The SOS MAS innovation has been shown to greatly improve public satisfaction. Agencies are encouraged to improve their communication and outreach efforts as well as create SOS MAS innovations that maximize the advantages of innovations that meet community needs.